The Uniform Scattered Fields from a Parabolic Surface with the Boundary Diffraction Wave Theory - Yalcin, Ugur; Altingoz, Can (Photonics Letters of Poland, 2017)
The uniform scattered fields of the cylindrical wave from a parabolic surface are obtained with the theory of the boundary diffraction wave (TBDW). The non-uniform diffracted field is calculated with the regenerated vector potential and rearranged by considering the Fresnel function to obtain the uniform solution. The uniform scattered fields are calculated as the sum of the diffracted and the geometrical optic fields. The numerical analyses of the diffracted and scattered fields in both uniform and non-uniform solutions are in harmony with the literature. Full Text: PDF References Baker, B. B., Copson, E. T., The mathematical theory of the Huygens’ principles, 2nd Edition, Oxford Press, (1950). DirectLink Lit, J. W. Y. "Boundary Diffraction Waves due to a General Point Source and Their Applications to Aperture Systems" J. Modern Opt., 19, 1007 (1972). CrossRef Otis, G., "Application of the Boundary Diffraction Wave Theory to Gaussian Beams", J. Opt. Soc. Am., 64, 1545 (1974). CrossRef Ganci, S., "Boundary Diffraction Wave Theory for Rectilinear Apertures", Eur. J. Phys., 18, 229 (1997). CrossRef Longhurst, R. S., Geometrical and Physical Optics, 2nd Edition, Longmans [London], (1968). DirectLink Maggi, G. A., "Sulla Propagazione Libra e Perturbata delle Onde Luminose in un Mezzo Izotropo", Ann. di Mat. IIa, 16, 21 (1888). Rubinowicz, A., "Die Beugungswelle in der Kirchoffschen Theorie der Beugungsercheinungen", Ann. Physik, 4, 257 (1917). CrossRef Miyamoto, K. and Wolf, E., "Generalization of the Maggi-Rubinowicz Theory of the Boundary Diffraction Wave Part I", J. Opt. Soc. Am., 52, 615 (1962). CrossRef Miyamoto, K., Wolf, E., "Generalization of the Maggi-Rubinowicz Theory of the Boundary Diffraction Wave Part II", J. Opt. Soc. Am., 52, 626 (1962). CrossRef Born, M. and Wolf, E. Principles of Optics Seventh edition, Cambridge Univ. Press, (1999). CrossRef Alt?ngöz, C., Yalç?n, U. "Calculation of the Diffracted Waves from the Edge of an Opaque Cut Cylinder by the Boundary Diffraction Wave Theory", Journal of the Faculty of Eng. and Arch. of Gazi University, 28, 85, (2013). CrossRef Yalç?n, U. "Yutucu Yar?m Düzlemin Kenar?ndan K?r?nan Üniform Alanlar?n S?n?r K?r?n?m Dalgas? Teorisi ile Hesab?", Çankaya Üniversitesi 2.Müh. ve Tek. Sempozyumu, (2009). (In national language) CrossRef Lee, S. W. and G. A. Deschamps, uniform asymptotic theory CrossRef Lee, S. W., "Comparison of uniform asymptotic theory and Ufimtsev’s theory of electromagnetic edge diffraction," IEEE Trans. Antennas & Propagat., Vol. 25, 162-170, 1977. CrossRef Yalç?n, U., "Uniform Scattered Fields of the Extended Theory of Boundary Diffraction Wave for PEC Surfaces", PIER M, 7, 29, (2009) DirectLink Yalç?n, U., "Analysis of Diffracted Fields with the Extended Theory of the Boundary Diffraction Wave for Impedance Surfaces", Appl. Opt., 50, 296 (2011). CrossRef Sarn?k, M., Yalç?n, U., "Uniform scattered fields from a perfectly conducting parabolic reflector with modified theory of physical optics", Optik-International J. for Light and Electron Opt., 135, 320 (2017). CrossRef Sarn?k, M., Yalç?n, U., "Modified theory of physical optics and solution for scattering fields from a perfectly conducting parabolic reflector", 16th Int. Conference on Math. Met. in Electromagnetic T. (MMET), July 5-7, Ukraine, 349 (2016). CrossRef Umul, Y. Z., Yalç?n, U. "Asymptotic Evaluation of The Edge Diffraction In Cylindric Paraboloidal Surface Antennas", Mathematical & Computational App., 8, 143 (2003). CrossRef Yalç?n, U., "Scattering from a cylindrical reflector: modified theory of physical optics solution", J. Opt. Soc. Am. A, 24, 502 (2007). CrossRef